Transformasi Administrasi Perkantoran melalui Literasi Digital: Pelatihan dan Penerapan Teknologi untuk Siswa SMK Muhammadiyah Kadungora - Hermansyah; Suherman, Ade; Darojat, Arik; Melati, Prima; Hermanto, Odang; Subata, Latansa; Bhakti, Demmy Dharma; Denni, Irdam (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2024)
In today's digital era, digital literacy has become a crucial factor across various sectors, including office administration. The transformation of office administration through digital literacy can enhance efficiency, productivity, and students' work skills. This study aims to evaluate the effectiveness of digital literacy training in the transformation of office administration at SMK Muhammadiyah Kadungora. The research employs a quantitative approach with a quasi-experimental design. Data were collected through questionnaires, interviews, and observations before and after the training. Data analysis was conducted using descriptive and inferential statistical techniques to assess changes in students' skills and understanding. The findings indicate that digital literacy training significantly improved students' understanding of office administration and related technical skills. Students experienced a notable increase in their ability to use office software, manage data, and communicate digitally.